Analisis Filsafat Hukum Pada Aturan Penghapusan Kekerasan Seksual Dalam Undang-Undang No. 12 tahun 2022 - Moh. Fudholi; Mohsi Mohsi (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2025)
Sexual violence is a crime against humanity that has long been a serious issue in society. Its impact not only harms individual victims but also creates broader social injustice. The government has made efforts to address this issue through various regulations, one of which is Law No. 12 of 2022 on the Prevention of Sexual Violence. This law aims to provide stronger legal protection for victims and prevent the occurrence of sexual violence in society. This study analyzes the philosophical aspects of this regulation using a legal philosophy and legislative approach. The analysis highlights the concepts of justice, human rights, legal ethics, and social responsibility in the implementation of this policy. Additionally, this study evaluates the effectiveness of the regulation in achieving its objectives and the challenges faced in its implementation. By understanding the philosophical foundations underlying this regulation, it is expected that Indonesia’s legal system can be further strengthened to provide better protection and justice for victims of sexual violence.